Unlocking User Satisfaction: A Delone & Mclean Is Success Model Approach To It Helpdesk Ticketing System Adoption - Niky Purnama Putra; Astari Retnowardhani (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The IT Helpdesk Ticketing System application is used to submit requests for IT services and handle technical problems related to these services. This research aims to understand the factors that influence user satisfaction with this application, which is triggered by user dissatisfaction. The research method used is qualitative using the DeLone & McLean IS Success Model, which is implemented through the Partial Least Squares Structural Equation Modeling (SEM) framework. The research was conducted on 231 respondents who were surveyed online. The results showed that system quality, service quality, and level of system usage significantly affect user satisfaction. System and service quality contribute positively to user satisfaction, while the level of system usage also has a key role in determining the level of satisfaction. The implications of the findings emphasize the importance of paying attention to these aspects in system development and improvement, while increasing the level of usage to meet the needs and increase user satisfaction more effectively.